Інтелектуальна власність як конкурентний ресурс промислового підприємства - Маслак, Марія Володимирівна (Національний технічний університет "Харківський політехнічний інститут", 2023)
У статті розглянуто теоретико-методичні питання конкурентного використання об’єктів інтелектуальної власності у виробничо-підприємницькій діяльності українських промислових підприємств. Визначено та обґрунтовано три основні напрямки розгляду терміну «інтелектуальна власність»: нормативно-правовий, економічний та управлінський. Рекомендоване автором до наукового обігу визначення терміну «інтелектуальна власність» практично поєднує в собі і правову, і економічну, і організаційну, і управлінську складові цієї дефініції, що досить точно відтворює організаційно-виробничі процеси розробки, розповсюдження та споживання об’єктів інтелектуальної власності та створених з їх використанням ринкових продуктів.

The article examines the theoretical and methodological issues of competitive use of intellectual property objects in the production and business activities of Ukrainian industrial enterprises. Three main areas of consideration of the term "intellectual property" are defined and substantiated: regulatory, economic, and managerial. The definition of the term "intellectual property" recommended by the author for scientific circulation practically combines the legal, economic, organizational, and managerial components of this definition, which quite accurately reproduces the organizational and production processes of development, distribution, and consumption of intellectual property objects and created with their use of market products. It has been proven that intellectual property objects are a significant factor in creating competitive advantages of an industrial enterprise, as they allow to ensure the protection of the results of innovative activity, a monopoly position on the market on this basis, and to use the period of protection to expand the volume of sales of products on the markets, form and consolidate the brand of the industrial enterprise enterprises. Individual components of the manifestation of the specificity of intellectual property and its objects in the industrial production of our country have been studied in detail, to which the author attributes a number of important specific features that contribute to the greatest extent to the improvement of the competitive positions of an industrial enterprise on the domestic and international market. The author attributed to them: an intangible form of representation, the possibilities of identification for establishing the object of the right, its potential includes both scientific and technical and production components, alienation of a special kind: copyright is preserved, individual patent right is protected, individual copyright is protected, individual copyright, a collective component of property rights. The identified features of the practical use of intellectual property objects at industrial enterprises make it possible for them to be more effectively used in various types of manufactured products. The use of intellectual property has both competitive advantages and certain disadvantages for an industrial enterprise. At the same time, competitive advantages are more important, strategically significant, long-term, but have a high degree of volatility and commercial risk and urgently need more balanced and more justified management decisions.
Intellectual property as a competitive resource of an industrial enterprise
Keywords: ринок; конкуренція; інтелектуальна власність; система управління; особливості використання; створення; дистрибуція; market; competition; intellectual property; management system; features of use; creation; distribution